Numerical method for the solution of linear boundary-value problem for integrodifferential equations based on spline approximations - Iskakova, N. B.; Assanova, A. T.; Bakirova, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.642 We propose a numerical method for the solution of linear boundary-value problem for system of integrodifferential equations.This method is based on the approximation of the integral term by a cubic spline and reduction of the original problem toa linear boundary-value problem for a system of loaded differential equations. We also propose new algorithms for findingthe numerical solution and a method for the construction of approximate solution to the approximating boundary-valueproblem.